Réponses

2014-05-06T19:31:35+02:00
Bonsoir

A = (x+4)(x+3) = x² + 3x +4x +12 = x² +7x +12
B = (y+3)(2y+8) = 2y² +8y +6y +24 = 2y² +14y +24
C = (y+3)(2y+8)= c'est la même
D = (-7t+8)(3-5t)
= - 21t + 35t² + 24 - 40t =35t² - 61t +24

Meilleure réponse !
2014-05-06T19:32:49+02:00
Développer et réduire :

A = (x + 4) (x + 3)
A = x² + 3x + 4x + 12
A = x² + 7x + 12

B = (y + 3) (2y + 8)
B = 2y² + 8y + 6y + 24
B = 2y² + 14y + 24

C = (y + 3) (2y + 8)
C = 2y² + 8y + 6y + 24
C = 2y² + 14y + 24

B = C

D = (-7t + 8) (3 - 5t)

D = -21t + 35t² + 24 - 40t
D = 35t² - 61t + 24